High-fat, high-sucrose, and combined high-fat/high-sucrose diets effects in oxidative stress and inflammation in male rats under presence or absence of obesity - Kobi, Jéssika Butcovsky Botto Sarter; Matias, Amanda Martins; Gasparini, Patrícia Vasconcelos Fontana; Torezani-Sales, Suellem; Madureira, Amanda Rangel; da Silva, Daniel Sesana; Corrêa, Camila Renata [UNESP]; Garcia, Jéssica Leite [UNESP]; Haese, Douglas; Nogueira, Breno Valentim; de Assis, Arícia Leone Evangelista Monteiro; Lima-Leopoldo, Ana Paula; et al. (Wiley, 2023)
The study examines the influence of three types of hypercaloric diets on metabolic parameters, inflammatory markers, and oxidative stress in experimental model. Male Wistar rats (n = 40) were randomized in control (C), high-sucrose (HS), high-fat (HF), and high-fat with sucrose (HFHS) for 20 weeks. Nutritional, metabolic, hormonal, and biochemical profiles, as well as histological analysis of adipose and hepatic tissues were performed. Inflammation and oxidative stress were determined. HF model caused obesity and comorbidities as glucose intolerance and arterial hypertension. In relation to hormonal and biochemical parameters, there was no significant difference between the groups. All groups showed increased deposition of fat droplets in the hepatic tissue, even though adipocyte areas were similar. Biomarkers of oxidative stress in serum and adipose tissues were similar among the groups. HF model was effective in triggering associated obesity and comorbidities in male rats, but all hypercaloric diets were unable to promote oxidative stress and inflammation.
Keywords: diets; inflammation; obesity; oxidative stress; rats